The Relationship Between Big Five Personality Traits and Counterproductive Work Behaviour - Ismail, Fadillah; Ashfaq, Muhammad; Aisyah Panatik, Siti; Jaes, Lutfan; Mee Yan, Wee (International Journal of Engineering and Technology, 2018)
Employees are a group that plays an important role in determining the quality, reputation, and performance of an organization. Personality traits within them were seen to predict employees’ behavior towards organizations. This research aims to examine the relationship between big five personality traits and counterproductive work behaviour (CWB) among employees in the manufacturing industry. Five research hypotheses were examined while considering the Big Five dimensions of personality, which are extraversion, agreeableness, conscientiousness, neuroticism, and openness, which are believed to influence the employees’ CWB. Present research specifically focuses on individual (CWB-I). 200 employees in the furniture manufacturing industry at Muar, Johor were randomly selected to complete the Big Five questionnaire. Software PLS -SEM was used to analyse the data collected. For CWB-I, the result showed negative relationship of neuroticism and agreeableness, whereas positive relationship with extraversion, openness and conscientiousness.